Implementasi Barang Bukti Petunjuk Oleh Hakim dalam Menjatuhkan Putusan Tindak Pidana Pembunuhan - Sulistiyono, Noor; Perdana, Fadjrin Wira; Irwan, Irwan; Tungkup, Doharman Lumban; Miran, Miran (Jurnal Indonesia Sosial Sains, 2022)
Indonesia is a legal state where all forms of citizen actions have legal consequences. Public law in Indonesia consists of criminal law and civil law. One of the criminal laws is murder. In the process of resolving cases of murder crimes, evidence is required. One of the evidence used is evidence of instructions. The purpose of this study is to examine the use of evidence as one of the judges' considerations in giving a decision. This research uses descriptive qualitative method with juridical-normative approach and literature study. The data used are secondary data taken from various literatures and scientific publications. The results showed that in several cases of murder in several District Courts, judges used evidence as a basis for consideration in giving criminal law decisions. Several District Courts in Indonesia that use evidence as a judge's consideration in making decisions include the Solok District Court, Padangsidimpuan District Court, Semarang District Court, and Simalungun District Court.